When Is a Plasmodium-Infected Mosquito an Infectious Mosquito?. Issue 8 (August 2020) - Graumans, Wouter; Jacobs, Ella; Bousema, Teun; Sinnis, Photini
Abstract : Plasmodium parasites experience significant bottlenecks as they transit through the mosquito and are transmitted to their mammalian host. Oocyst prevalence on mosquito midguts and sporozoite prevalence in salivary glands are nevertheless commonly used to confirm successful malaria transmission, assuming that these are reliable indicators of the mosquito's capacity to give rise to secondary infections. Here we discuss recent insights in sporogonic development and transmission bottlenecks for Plasmodium . We highlight critical gaps in our knowledge and frame their importance in understanding the human and mosquito reservoirs of infection. A better understanding of the events that lead to successful inoculation of infectious sporozoites by mosquitoes is critical to designing effective interventions to shrink the malaria map. Highlights: The discrepancy between exposure to infected mosquito bites and malaria incidence suggests a transmission bottleneck that is currently understudied. Recent studies from non-human malaria models are indicative of a minimum salivary gland sporozoite density that is required to achieve infection following a mosquito bite. Infection-induced alterations in blood-feeding behavior of mosquitoes may influence natural transmission dynamics.